Police conflict management, Volume I: challenges and opportunities in the 21st century - Staller, Mario; Körner, Swen; Zaiser, Benni (Palgrave Macmillan, 2023)
Chapter 1: 21st Century Policing: Between Evidence-Based Practice and Reflexivity -- Chapter 2: Police trust and legitimacy in modern societies: Fairness in interactions as a key -- Chapter 3: Danger, Fighting and Badassness: A Social Systems Perspective on Narratives and Codes in Police Conflict Management -- Chapter 4: Policing in the light of Social Dominance Theory and Social Distance Theory of Power -- Chapter 5: Psychological Aspects of the Use of Firearms by the Police -- Chapter 6: Prevalence and correlates of violence against law enforcement officers in the United States: A national portrait -- Chapter 7: Police Conflict Management and the Phenomena of Suicide-by-Cop in North America -- Chapter 8: A Feminist Ethics of Care Approach to De-escalation in Policing -- Chapter 9: Barriers to Effective De-escalation -- Chapter 10: Applying the Interpersonal Circumplex Model to De-Escalative Communication in Police Service -- Chapter 11: Nonverbal Behavior and Appearance of Police Officers in the Police Service -- Chapter 12: Effective Police Negotiation: Synthesising the Strategies and Techniques That Promote Success Within Hostage or Crisis Situations -- Chapter 13: Community relations and policing: A communication accommodation theory perspective -- Chapter 14: Policing Hate Rallies -- Chapter 15: Police Conflict Management in South Africa: An Autoethnographic Reconnaissance -- Chapter 16: Police Crowd Management in South Africa: Efforts and Challenges of De-Escalation -- Chapter 17: Police legitimacy in Russia: Explaining millennials' obligation to obey and willingness to cooperate.